(untitled) (Fiep Bulletin - online, 2013)
The society is modulated culturally by the social one, economic politician and. Inserted they we place the sportive context, which together possess one weight with the medias of mass in the construction of symbols in the most diverse societies giving to them specificities, as for example: it concerns attributes in the formation of the social representations, it supports religiosities and it spreads mythical and mystics thoughts. The Sport, in a generalized manner, in the last few decades, became field of interest of diverse sciences due to repercussion and influences in the society and the individuals. Its specific dad openly demonstrates to interests and ideologies in the search for the victory all the cost to make of the aficionado, the spectator and the precursory activists of the most varied human behaviors. Soon, the sport becomes field of research of Social Sciences, here of sociology, in the attempt to explain social behaviors, symbols, signs, actions, emotions, representations through the times, and in the present concern that is the violence.